Entrepreneurship Education and Training Programs around the World : Dimensions for Success - Valerio, Alexandria (Washington, DC: World Bank, 2014)
Entrepreneurship has attracted global interest for its potential to catalyze economic and social development. Research suggesting that certain entrepreneurial mindsets and skills can be learned has given rise to the field of entrepreneurship education and training (EET). Despite the growth of EET, global knowledge about these programs and their impact remains thin. In response, this study surveys the available literature and program evaluations to propose a Conceptual Framework for understanding the EET program landscape.